Potential effects of adverse childhood experiences on school engagement in youth: a dominance analysis - Nathaniel J. Webb; Thaddeus L. Miller; Erica L. Stockbridge (BMC, 2022)
Abstract Background Adverse childhood experiences (ACEs) can have severe negative impacts on childhood and adult health via worsened school engagement and educational outcomes. This study seeks to identify the relative importance of various ACEs in predicting school engagement. Methods We analyzed data from the National Survey of Children's Health for school-aged children (ages 6-17) for 2018 and 2019. The primary outcome was school engagement, measured through three variables: repeating a grade, doing required homework, and caring about doing well in school. We conducted three logistic regression models with dominance analyses to identify the relative importance of ACE variables in predicting school engagement outcomes. Results In unadjusted and adjusted dominance analyses, parental incarceration was the most important ACE in predicting repeating a grade. Living in a household in which it was hard to cover basics like food or housing was the most important ACE in predicting doing required homework and caring about doing well in school. Discussion Our study points toward the large influence of out-of-school factors on school engagement. Parental incarceration and economic hardship, the most important predictors of engagement, are issues that can be addressed and mitigated through policy interventions. With limited funds available for education and public health interventions, it is crucial that these two ACEs be priority considerations when developing policy. A multi-faceted approach that reduces the incarcerated population, encourages economic well-being, and emphasizes early-childhood education has the potential to significantly improve school engagement in vulnerable populations and ultimately advance social equity.